Colorectal anastomotic leak: transcriptomic profile analysis. Issue 3 (30th January 2021) - van Praagh, J B; de Wit, J G; Olinga, P; de Haan, J J; Nagengast, W B; Fehrmann, R S N; Havenga, K
Abstract: Background: Anastomotic leakage in patients undergoing colorectal surgery is associated with morbidity and mortality. Although multiple risk factors have been identified, the underlying mechanisms are mainly unknown. The aim of this study was to perform a transcriptome analysis of genes underlying the development of anastomotic leakage. Methods: A set of human samples from the anastomotic site collected during stapled colorectal anastomosis were used in the study. Transcriptomic profiles were generated for patients who developing anastomotic leakage and case-matched controls with normal anastomotic healing to identify genes and biological processes associated with the development of anastomotic leakage. Results: The analysis included 22 patients with and 69 without anastomotic leakage. Differential expression analysis showed that 44 genes had adjusted P < 0.050, consisting of two upregulated and 42 downregulated genes. Co-functionality analysis of the 150 most upregulated and 150 most downregulated genes using the GenetICA framework showed formation of clusters of genes with different enrichment for biological pathways. The enriched pathways for the downregulated genes are involved in immune response, angiogenesis, protein metabolism, and collagen cross-linking. The enriched pathways for upregulated genes are involved in cell division. Conclusion: These data indicate that patients who develop anastomotic leakage start the healing process with an error at the level of gene regulation at the time of surgery. Despite normal macroscopic appearance during surgery, the transcriptome data identified several differences in gene expression between patients who developed anastomotic leakage and those who did not. The expressed genes and enriched processes are involved in the different stages of wound healing. These provide therapeutic and diagnostic targets for patients at risk of anastomotic leakage. Abstract : Anastomotic leakage (AL) remains a frequent complication in patients with a colorectal anastomosis, despite known risk factors. This transcriptomic analysis showed that patients who develop AL have a status or a trait at the level of gene regulation at the time of surgery that predisposes them to leakage. Anastomotic leakage (AL) is still a frequent complication in patients with a colorectal anastomosis, despite known risk factors. Our transcriptomic analysis shows that patients developing AL have a status or a trait at the level of gene regulation at the moment of surgery that predisposes them for AL. Gene expression predicts leaks